2001
DOI: 10.1210/jcem.86.4.7415
|View full text |Cite
|
Sign up to set email alerts
|

C-peptide and Glucagon Profiles in Minority Children with Type 2 Diabetes Mellitus

Abstract: The present study was conducted to determine the extent of insulin deficiency and glucagon excess in the hyperglycemia of type 2 diabetes in children. The incidence of type 2 diabetes mellitus in children and adolescents has increased substantially over the past several years. Because insulin and glucagon action both regulate blood glucose concentration, we studied their responses to mixed meals in children with type 2 diabetes. Subjects were 24 patients with type 2 diabetes compared with 24 controls, aged 9--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…Insulin secretion in response to glucose that is partially defective could be impaired in addition by glucose and/or lipotoxicity. Moreover, glucagon, the main ketogenic hormone in humans is increased in Type II diabetes and a relative hyperglucagonaemia was also evidenced in African-American children with acute-onset Type II diabetes [16]. We therefore hypothesise that this atypical diabetes is a subtype of Type II diabetes, which develops in patients with high sensitivity to glucotoxicity or lipotoxicity, or with dysregulation of glucagon secretion.…”
Section: For Debatementioning
confidence: 93%
“…Insulin secretion in response to glucose that is partially defective could be impaired in addition by glucose and/or lipotoxicity. Moreover, glucagon, the main ketogenic hormone in humans is increased in Type II diabetes and a relative hyperglucagonaemia was also evidenced in African-American children with acute-onset Type II diabetes [16]. We therefore hypothesise that this atypical diabetes is a subtype of Type II diabetes, which develops in patients with high sensitivity to glucotoxicity or lipotoxicity, or with dysregulation of glucagon secretion.…”
Section: For Debatementioning
confidence: 93%
“…Another study in 9-to 20-year-old type 2 diabetic patients revealed relative hypoinsulinemia and hyperglucagonemia in response to a mixed liquid meal tolerance test (20). However, the insulin deficiency was not expressed relative to the degree of insulin resistance (not measured).…”
Section: Correlationsmentioning
confidence: 95%
“…1) [25]. When youth with T2DM are compared with non-diabetic control subjects, stimulated C-peptide levels are lower while glucagon levels are not different [32, 33]. Similarly, insulin response to intravenous glucose stimulation is significantly deficient in adolescents with T2DM compared with non-diabetic adolescents [33].…”
Section: Clinical Characteristics Of T2dm In Childrenmentioning
confidence: 99%